2020
DOI: 10.1111/1346-8138.15256
|View full text |Cite
|
Sign up to set email alerts
|

Local and disease control for nasal melanoma treated with radiation and concomitant anti‐programmed death 1 antibody

Abstract: Mucosal melanoma of the nasal cavity is a rare disease that has been consistently associated with poor outcome. While complete surgical excision offers the only prospect of a cure, it is associated with a high risk of surgical morbidity due to the challenging anatomical location, and most patients still develop incurable metastatic disease. The efficacy of immunotherapy on mucosal melanoma is lower in comparison with cutaneous melanoma, and mucosal melanoma rarely has BRAF mutations. Although preclinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…54,55 In this review, we identified three single-center, retrospective studies that investigated radiotherapy combined with anti-PD-1 antibody. [49][50][51] The ORRs of the multimodal therapy were more than 50%, which were much higher than each single modality treatment. In addition, no grade 3 or more AEs occurred in patients receiving multimodal therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…54,55 In this review, we identified three single-center, retrospective studies that investigated radiotherapy combined with anti-PD-1 antibody. [49][50][51] The ORRs of the multimodal therapy were more than 50%, which were much higher than each single modality treatment. In addition, no grade 3 or more AEs occurred in patients receiving multimodal therapy.…”
Section: Discussionmentioning
confidence: 95%
“…The local control rate of the primary lesion and regional lymph nodes was 100% with a median PFS of 7.4 months. 50 Another retrospective study reported the efficacy and safety of combined radiotherapy and anti-PD-1 monoclonal antibodies for MM. 51 Four of the seven patients with MM achieved CR and PR (ORR = 57.1%) and grade 3 or more severe AEs were not observed.…”
Section: Anti-pd-1 Monoclonal Antibodies Combined With Radiotherapymentioning
confidence: 99%
“…To improve the lower clinical efficacy of PD1 in MCM, additional treatment options with PD1 should be explored; however, very few studies have examined PD1 in combination with other treatment modalities, and they have used small sample sizes. Four studies have tested the efficacy of PD1 plus radiotherapy, including a study recently reported by our group, 22 , 23 , 24 , 25 two studies have tested PD1 plus a vascular endothelial growth factor receptor (VEGFR) inhibitor, 26 , 27 and four studies explored the efficacy of PD1 + CTLA4. 6 , 16 , 17 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“… 22 Another retrospective study of 10 Japanese MCM patients that evaluated pembrolizumab plus radiotherapy showed an ILC rate of 100% and a median PFS of 7.4 months. 24 A retrospective study that evaluated the efficacy of PD1 plus radiotherapy in seven Japanese MCM patients noted an ORR of 57.1% and a 1-year PFS of 50%. 23 These studies mainly focused on ILC rate and did not include sufficient data regarding survival compared with PD1.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low incidence rate of disease and the limited number of published articles and clinical trials, this review has included all of the relevant articles and clinical trials available [10][11][12][13][14][15][16][17][18]. Because the radiotherapy methods and prognosis for patients with advanced brain metastases are poor, and there are relevant literature to systematically analyze studies on patients with brain metastases of melanoma [9,19], this meta-analysis does not include those studies.…”
Section: Study Selectionmentioning
confidence: 99%